Nanomaterials Toxicity and Risk Assessment - Soloneski, Sonia; Larramendy, Marcelo L. (IntechOpen, 2015)
This edited book, Nanomaterials - Toxicity and Risk Assessment, is a collection of current research and information on numerous advances on the toxicity and hazardous effects of nanomaterials, including theoretical and experimental approaches as well as nanotechnology applications in the field of medicine, pharmacology, and the manufacture of nanoscale materials. Based on the large number of nanomaterial applications, a careful understanding of the associated systemic and local toxicity is critically required.